Bright Aggregation-Induced-Emission Dots for Targeted Synergetic NIR-II Fluorescence and NIR-I Photoacoustic Imaging of Orthotopic Brain Tumors - SHENG, ZONGHAI (WILEY-V C H VERLAG GMBH, 2019)
10.1002/adma.201800766